Using n-toluenesulfuric acid salts as esterification catalysts - Мельник, Степан Романович; Дзіняк, Мар’яна Богданівна; Старчевський, Володимир Людвікович (Eastern-European Journal of Enterprise Technologies, 2013)
The influence of n-toluenesulfonic acid salts on technological parameters of the process of acetic and adipinic acids esterification by 1-butanol and 3-methylbutan-1-ol has been analyzed in non-stationary conditions. It has been determined, that using these kinds of catalysts, as compared to n-toluenesulfonic acid, provides reducing the dibutyl adipate and alkylacytates synthesis duration, lower acid number of reaction products and higher acid conversion with the concentration rate, proportional to the p-TSA. Although there is no need for the high catalyst concentration for achieving the effect, still it allows faster esterification process. The research has shown that low content of water, added to reagents in amount of 3-4 mass %, can reduce the dibutyl adipate and alkylacytates production duration almost by half without worsening its technological parameters. The effect of water influence lies in improvement of salt-catalyst solubility in reaction mixture at the initial reaction phase, that probably cuts the induction period of forming the catalyst–substrate complex. Further increasing of water content in the output reaction mixture causes low values of acid conversion. A series of cationic activities of n-toluene sulfonic acid salt metals in reaction of acetic acid esterification by 3-methylbutan-1-ol has been singled out. It has been found out that using aluminum and stannum n-toluene sulfates provides better technological parameters, than when using n-toluene sulfonic acid. The research results prove the effectiveness of using n-toluenesulfonic acid salts as esterification catalysts